Nosokomiale Pneumonien - Großmann, Joachim; Schulz-Stübner, Sebastian (DMW - Deutsche Medizinische Wochenschrift, 2020)
Nosocomial pneumonia is one of the leading entities of nosocomial infections in Germany and worldwide with invasive ventilation being one of the major risk factors. However nosocomial pneumonia without ventilator support is an underappreciated complication as demonstrated by prevalence studies of the European Centre for Disease Control in 2011 and 2016. Major general risk factors include old age, multi-morbidity, preexisting pulmonary disease, immunosuppression and abdominal or thoracic surgery. Evidence based prevention measures for ventilated patients include hand hygiene, aseptic handling techniques of the ventilator circuit, subglottic suctioning for patients intubated more than 72 hours, cuff pressure control, mouth and dental care, daily spontaneous breathing trials, use of sedation protocols and head of bed 30–45 degrees. For non-ventilated patients early mobilization and/or frequent position changes, correct use of feeding tubes and mouth care are key components. In preoperative patients training of a simple breathing exercise combined with mnemonic aids for its use in the postoperative period has been proven to be helpful.
Keywords: Frühmobilisation; postoperative pulmonale Komplikationen; Präventionsbündel; Cuffdruckmessung; early onset